Pemanfaatan E-GEPATAN untuk Administrasi Lahan Pertanian dan Distribusi Hasil Panen Petani - Muhamad Awiet Wiedanto Prasetyo; Riyatno Riyatno; Arif Riyandi; Fadiana Fadiana; Jamaludin Abdul Karim (Indonesian Journal of Community Service and Innovation, 2025)
The problem of the unavailability of a proper administrative and land-recording system was addressed by developing a digital-based recording system, E-GEPATAN, which can be utilized to systematically document land area, ownership, and land status. The implementation method began with data collection through interviews with the Plana Village Government and the Plana Jaya Farmers’ Group Association (Gapoktan), as well as observations on member registration and documentation of agricultural land, particularly rice fields. The results indicate that most of the predetermined targets were successfully achieved, including the documentation of 95% of agricultural land within E-GEPATAN, 82% of harvests recorded digitally, and 65 farmers actively using the marketing features. Following the facilitation and technical assistance through E-GEPATAN, farmers gradually adapted to the digital system, which allowed agricultural data recording to become more systematic and centrally monitored by Gapoktan as the primary manager. Behavioral changes among farmers were also observed, particularly in their newly established practices of soil quality testing through pH measurement, which had never been conducted before. These outcomes highlight that E-GEPATAN serves not merely as a recording platform but as a digital transformation instrument that promotes transparency, efficiency, and enhanced competitiveness in the agricultural sector of Plana Village